2011
DOI: 10.1002/acr.20345
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic determinants of disability and depression in patients with rheumatoid arthritis

Abstract: Objective To examine the relationship between functional limitation, socioeconomic inequality, and depression in a diverse cohort of patients with rheumatoid arthritis (RA). Methods The study design was cross-sectional and subjects were from the University of California, San Francisco RA Cohort. Patients were enrolled from 2 rheumatology clinics, an urban county public hospital and a university tertiary care medical center. Age, sex, race/ethnicity, disease activity, functional limitation, and medications we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
2
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(82 citation statements)
references
References 41 publications
4
74
2
2
Order By: Relevance
“…The QUEST-RA studies in 25 countries showed an association between gross domestic product and disease status, including physical disability and psychological health (39). Margaretten et al refer to a "vulnerable population" of RA patients where background poverty and high functional disability give rise to a high risk for mental illhealth (40).…”
Section: Discussionmentioning
confidence: 99%
“…The QUEST-RA studies in 25 countries showed an association between gross domestic product and disease status, including physical disability and psychological health (39). Margaretten et al refer to a "vulnerable population" of RA patients where background poverty and high functional disability give rise to a high risk for mental illhealth (40).…”
Section: Discussionmentioning
confidence: 99%
“…With notable exceptions [32,4043], few studies of SES and depression in patients with RA have measured multiple indicators of SES. Future studies need more complete and better markers of SES.…”
Section: Socioeconomic Factors Related To Depression In Patients With Ramentioning
confidence: 99%
“…Depression has been consistently associated with worse disease outcomes in patients with RA, including pain, tender joints, poor adherence to medication, increased healthcare service utilization, disability, and higher rates of early retirement [2,5,[39][40][41][42]. Conversely, several studies have demonstrated that functional disability and loss of valued activities, such as employment, are associated with an increased risk of depression [39,42,43]. In addition, depression has been identified as an independent risk factor for cardiovascular disease, myocardial infarction, suicide, and all-cause mortality in patients with RA [44,45].…”
Section: C Psychological Factors Influencing the Effectiveness Of mentioning
confidence: 99%